Missing in action: the genetic mysteries of extremely low HDL cholesterol - Sphitzen, Shoshi; Golomb, Mordechai; Mowaswes, Mohammad; Bitzur, Refael; Horowitz Cederboim, Smadar; Leker, Ronen R.; Gotkine, Marc; Chovers, Itai; Schurr, Daniel; Leitersdorf, Eran; Durst, Ronen (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHigh-Density Lipoprotein Cholesterol (HDL-C) plays a pivotal role in cardiovascular health, acting as a key component in lipid transport and atheroprotection. While low HDL-C levels in the general population are often the result of multifactorial causes, extremely low HDL-C levels (<20 mg/dl) are rare and may be attributed to underlying genetic defects. Mutations in genes such as LCAT, APOA1, and ABCA1—although exceedingly rare—have been linked to profound alterations in lipid metabolism, often resulting in significant morbidity and increased cardiovascular risk.MethodsIn this study, we used exome sequencing on patients with very low HDL-C.ResultsWe identified three patients with pathogenic mutations associated with genetic low HDL-C syndrome, including ABCA1 [NM_005502.4(ABCA1):c.4175 + 1G > T, chr:9 91757308° C > A, rs375247413], LCAT [NM_000229.2(LCAT):c.349G > A p.Ala117Thr, rs28940886], and APOA1 [NM_000039.3(APOA1):c.388A > T, p.Lys130*].DiscussionEach case presented a unique spectrum of clinical phenotypes, systemic complications, and biochemical abnormalities, illustrating the diverse impact of these genetic mutations. We provide a detailed analysis of the clinical and biochemical profiles of these patients, highlighting key aspects of disease manifestation and progression. This report underscores the importance of recognizing and characterizing rare genetic causes of low HDL-C, which may have profound implications for patient care and risk stratification.